2018
DOI: 10.1016/j.resuscitation.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Can early warning scores identify deteriorating patients in pre-hospital settings? A systematic review

Abstract: Very low and high EWS are able to discriminate between patients who are not likely and those who are likely to deteriorate in the pre-hospital setting. No study compared outcomes pre- and post-implementation of EWS so there is no evidence on whether patient outcomes differ between pre-hospital settings that do and do not use EWS. Further studies are required to address this question and to evaluate EWS in pre-hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 22 publications
5
75
0
1
Order By: Relevance
“…This generated a very homogeneous cohort since all the cases were assessed by the physician at the ALS and the purpose of selecting cases was to detect those cases with a risk of deterioration. Secondly, early mortality (within 48 hours) was determined as one of the result outcomes but we are aware that this time limitation in the inclusion of cases is partial and it may be very interesting to study mortality rates after seven or 30 days, or even in the longer term, but the objective of this study is to analyze the influence of the procedures carried out by the EMS at the scene or en route, such that mortality after two days does not seem to be an adequate solution and this is in line with similar publications [27,55,56].…”
Section: Limitationssupporting
confidence: 52%
“…This generated a very homogeneous cohort since all the cases were assessed by the physician at the ALS and the purpose of selecting cases was to detect those cases with a risk of deterioration. Secondly, early mortality (within 48 hours) was determined as one of the result outcomes but we are aware that this time limitation in the inclusion of cases is partial and it may be very interesting to study mortality rates after seven or 30 days, or even in the longer term, but the objective of this study is to analyze the influence of the procedures carried out by the EMS at the scene or en route, such that mortality after two days does not seem to be an adequate solution and this is in line with similar publications [27,55,56].…”
Section: Limitationssupporting
confidence: 52%
“…Scores are calculated from physiological observations, with higher scores indicating poorer health. Though developed for hospitals, studies of EWS in pre-hospital settings have been shown to predict outcomes such as hospital stay and mortality; [2][3][4][5][6] however, those studies were mostly in ambulance and non-UK settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is reluctance from GPs to adopt NEWS/NEWS2 for a number of reasons, such as a preference for observing symptoms, clinical instinct, and a lack of validated studies conducted in primary care; GPs also report time restraints restricting the appropriateness of a full set of observations. 16,17 There is currently little evidence about how NEWS in these settings influences patient outcomes, 4 though some is beginning to emerge. [2][3][4][5]13,16,18 The objective of this study was to investigate whether NEWS calculated at the point of GP referral to hospital affects timely process of care, that is, sicker patients seen faster, and to investigate clinical outcomes in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that EWS in pre-hospital settings could identify patients at risk of deterioration and in need of hospitalisation, with patients at low risk of deterioration safely managed at home [29].…”
Section: Formal Home Care Servicementioning
confidence: 99%
“…RNs experienced that identification of potentially life-threatening conditions for elderly patients, such as infections and sepsis, were identified and treated earlier with EWS [29,34].…”
Section: The Implementation Of Mews Has Improved Practicementioning
confidence: 99%